THE DEVELOPMENT OF STUDENT WORKSHEETS BASED ON SCIENTIFIC APPROACH FOR INCREASING OF CRITICAL THINKING SKILLS OF SENIOR HIGH SCHOOL GRADE XI NATURAL SCIENCE - Sri Wahyuni Sri Wahyuni; Evi Suryawati Evi Suryawati; Raja Husein Arief Husein Arief (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of this study is develop of student worksheets based on scientific approach for senior high school biology grade XI. This development consisted of eight student worksheets. This study was conducted in Biology Education Program and tryout in PMIPA Laboratorium of Teacher Training and Education University of Riau on May to December 2014. Validation sheets, student responses sheets and critical thinking skill sheets were used as data collection instruments. Validation sheets were filled by the internal and external vaidators. Student responses sheet were filled by students and critical thinking skill sheet were filled by observers. Collected datas were analyzed by descriptive statistics. The result of this worksheets development showed that the student worksheets were very valid with score 3.6-3.7. Student responses to the worksheet were 35.5% of very good, 41.2% of good and 25.5% of good enough. Based on study result, the development of student worksheets based on scientific approach was done with 4D model that consists of define, design, develop and disseminate. Based on validation result, this students worksheets based on scientific approach could be implemented with filed test.Key words: Critical Thinking, Development, Student Worksheet Based On Scientific Approach